The gap between what patients know and desire to learn about their cardiac implantable electronic devices. Issue 1 (5th December 2019) - Patel, Divyang; Hu, Peter; Hilow, Henry; Lambert, Cameron T.; Moufawad, Michelle; Poe, Stacy; Hussein, Ayman A.; Baranowski, Bryan; Bhargava, Mandeep; Rickard, John W.; Cantillon, Daniel J.; Saliba, Walid; et al.
Abstract: Background: Advancement of digital technology now allows patients to have access to data from their cardiac implantable electronic devices (CIEDs). However, patients' understanding regarding CIED data and perceived personal usability remain unclear. The present study is a prospective survey to examine patients' understanding of their CIEDs and their perception of what is important. Methods: We screened 400 patients between July and December 2018 who presented to our outpatient clinic for a CIED interrogation. Patients received a one‐page questionnaire asking baseline demographics, their perception about their own knowledge about their device, and multiple‐choice questions in seven basic categories: type of CIED, original indication, functionality, manufacturer, number of active leads, estimated battery life, and number of shocks received. We compared these answers to their interrogation reports to assess accuracy. We also asked participants what they would like to be aware of regarding their CIED. Results: From this cohort, 344 of 400 (86%) (62.9 ± 12.8 years and 64 % males) agreed to take the survey and were included in the analysis. At baseline, 63.2% agreed or strongly agreed that they were knowledgeable about their devices. The overwhelming majority of patients demonstrated CIED knowledge deficits in at least one content area ( n  = 294, 86%), or more than two content areas ( n  = 176, 51%). Patients agreed or strongly agreed that they had a desire to have information regarding each of the following: battery life (84%), activity level (79%), heart rate trend (75%), and ventricular arrhythmias (74%). Conclusion: There is a large discrepancy in patients' level of knowledge regarding their CIEDs and their wish to know more details. Future technologies should satisfy providers' goals to educate their patients with basic information and fulfill patients' desire to obtain more data from their CIEDs.